PENGEMBANGAN BAHAN AJAR QUADCOPTER SEBAGAI PENUNJANG MATERI PEMBELAJARAN PID CONTROL PADA MAHASISWA TEKNIK ELEKTRO - Anggara, Fatih Tri; Achmad , Fendi; Wiyono, Agus; Kholis , Nur (Jurnal Pendidikan Teknik Elektro, 2025)
This research develops quadcopter-based teaching materials as a support for Proportional-Integral-Derivative (PID) control learning materials for Electrical Engineering students. The problem behind this study is the lack of innovation in the PID control learning method which generally uses line tracers, so that it has the potential to reduce student learning motivation. This research aims to develop new teaching materials that are more interesting and relevant to technological developments. The research method used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The user interface is made easier to use for people are new to PID control. Changes in the PID value can be input directly in the available columns. The results of the study showed that the quadcopter teaching materials were very practical with an average student response questionnaire score of 89.3%. From the evaluation of effectiveness based on the ARCS (Attention, Relevance, Confidence, Satisfaction) model, an average score of 91.5% was obtained, indicating a very high level of effectiveness in increasing the understanding and motivation of Electrical Engineering students. The flight test also showed a mission success rate between 66-93% with a measurable range of PID parameter values. The normality test and the T test showed a significant difference between the use of quadcopter and line tracer teaching materials in increasing learning motivation. It can be concluded that the development of quadcopter teaching materials is effective and practical as a support for PID control learning, and is able to increase student learning motivation.